Administration Response of Milkfish Rinsed Water on The Growth and Production of Celery (Apium graveolens L.) - Rahman Hairuddin; M. Mutmainnah; D. Dandi (Universitas Sembilanbelas November Kolaka, 2022)
This study aimed to determine growth and production responses of celery (Apium graveolens L.) after the administration of milkfish rinsed water. This study was perfomed in the Experimental Land, Faculty of Agriculture, Cokroaminoto University, Palopo on June – August, 2022. Experimental method used in this study was a completely randomized design, containing six treatments and four replications (24 experimental units). Treatments in this study contained several milkfish rinsed water administration doses, namely P0 = without rinsed water administration (control), P1 = 250 ml/polybag, P2 = 300 ml/polybag, P3 = 350 ml/polybag, P4 = 400 ml/polybag, and P5 = 450 ml/polybag. The results showed that the milkfish rinsed water administration significantly affect plant height, number of leaves, and number of buds, but obtaining no significant effect on wet weight. The best treatment was found in the P3 treatment with average plant height of 25.30 cm, 149.75 leaves, 6.75 buds, and 59.33 g wet weight